Preparação e estudo de nanocompósitos com grafenos para aplicação em armazenagem eletroquímica de energia - Neuma das Mercês Pereira (2018)
In this work, the study of carbon nanomaterials and ionic liquids was conducted aiming the production of electrochemical double electric layer capacitors (supercapacitors) with improved electrochemical properties such as wettability, electrolyte /electrode compatibility, capacitance, and energy and power densities. The development of carbon nanomaterials electrodes that provide desirable conductivity and porosity characteristics, which guarantees an easy access of electrolyte ions to their surface, is a challenge to be overcome in supercapacitors. This challenge is especially relevant in systems with ionic liquid (IL) based electrolytes due to the large volume of ions. In a first stage, the study of the synthesis of graphite oxide (GrO) and graphene oxide (GO) by microwave was carried out with the objective of obtaining the carbon nanomaterials to be used in the development of the later works with the optimization of the process of their synthesis. In the second stage, the study of graphene oxide (GO)incorporation in different ILs was carried out, aiming the construction of a composite electrolyte that would provide greater compatibility of the electrolyte with the graphene electrode. Among the ILs studied, triethylsulfonium bis(trifluoromethylsulfonyl)imide ([SET3][TFSI]) showed higher conductivity values and enhanced electrochemical stability. Supercapacitors based on pure ILs and 0.1 wt% ILs-GO were investigated with reduced graphene oxide (rGO) as electrode. The supercapacitor rGO/[SET3][TFSI]/rGO showed a capacitance of 95.8 F g-1, while a capacitance of 125.3 F g -1 was obtained for the supercapacitor rGO/[SET3][TFSI]-GO/rGO, both characterized by cyclic voltammetry (CV) with 5 mV.s-1 scan rate performing at a 2.5V. These results show 31% capacitance increasing due to the GO presence in ILs. SEM images indicated that the ILs-GO composite electrolyte increases the IL compatibility with the rGO electrode, favoring the electrolyte ions accessibility to the electrode surface. In the third stage of this work, it was proposed the synthesis of rGO compositeswith ionic liquid incorporated onto its surface for application as electrodes for supercapacitors. The materials were synthesized using a single stage microwave thermal expansion and a chemical reduction using hydrazine as the reducing agent. The thermal, morphological and electrochemical properties of these materials were studied in order to establish structure-property correlations. Among the materials synthesized by thermal expansion, the supercapacitor based on RGO/IL-150 showed 13.7 F g-1 capacitance value. This value is higher than the other materials, while the material synthesized via chemical reduction, IL, showed a capacitance of 70 F g-1, both being characterized byCV with 5 mV s-1 scan rate performing in 3.0 V. Therefore, the carbon nanomaterials developed in this work and the constructedsupercapacitors showed good electrochemical properties, which highlights its potential application for electrochemical supercapacitors preparation.